ANALISIS KELAYAKAN DESAIN PEMBELAJARAN MINYAK BUMI MENGGUNAKAN MODEL RADEC BERORIENTASI STEM UNTUK MENINGKATKAN KREATIVITAS DAN BERPIKIR KRITIS SISWA DAN BERPIKIR KRITIS SISWA - Wulandari, - (2021)
The purpose of this research is to produce a validated petroleum learning design that uses the STEM-oriented RADEC model to increase creativity and critical thinking. The research method used is descriptive evaluative. This study involved 2 observers for the TCOF test, 2 experts and 1 senior teacher for the internal feasibility test and 9 high school students of class XI for the external feasibility test. The instrument used was the TCOF, a feasibility test for the oil learning design and a student questionnaire. Furthermore, the data obtained is described and evaluated. The feasibility test and questionnaire are categorized according to the interpretation of Riduwan's score. Meanwhile, the TCOF analysis is categorized according to the interpretation of the Al Abdali & Al Balushi scores. Furthermore, the results of each analysis were re-evaluated. Based on the external and internal feasibility tests carried out, this learning design is suitable for increasing students' creativity and critical thinking. Keywords: Learning Design, RADEC, Creativity, Critical Thinking, Petroleum.